Design of experiments as a valuable tool for biopharmaceutical analysis with (imaged) capillary isoelectric focusing. Issue 18 (21st June 2019) - Kahle, Julia; Stein, Matthias; Wätzig, Hermann
Abstract: Capillary isoelectric focusing is indispensable for characterizing charge heterogeneity and isoelectric points of biopharmaceuticals. However, there are many influencing parameters and therefore method development is challenging. This study was performed to obtain an in‐depth understanding of the imaged CIEF methodology by applying a design of experiments approach. To describe the parameter's effects as objectively as possible, a polynomial regression model was derived for the most important responses. For this purpose, the reference monoclonal antibody suggested by the National Institute of Standards and Technology (NISTmAb) was used as test molecule. The total concentration and the mixing ratio of two types of carrier ampholytes and the added amounts of urea andl ‐arginine were selected as factors. The effects of these factors on 13 different responses such as resolution or p I values were investigated. In order to reduce the total number of experiments, ad ‐optimal design with 20 different parameter combinations and six replicates each was chosen. The most significant effects of the four factors were shown for the parameters related to separation efficiency and peak position. In addition, the extent of the factor's effect could be assessed. Depending on the selected factor combination, the p I value can differ up to approximately 0.15 p I units and the resolution value between main peak and adjacent basic peak can range from approximately 1.6 to 2.5, for example.